A platelet-derived hydrogel improves neovascularisation in full thickness wounds. (December 2021) - Rahman, Md. M.; Garcia, N.; Loh, Y.S.; Marks, D.C.; Banakh, I.; Jagadeesan, P.; Cameron, N.R.; Yung-Chih, C.; Costa, M.; Peter, K.; Cleland, H.; Akbarzadeh, S.
Abstract: Platelets are a reservoir of growth factors, cytokines and chemokines involved in spontaneous wound repair. In this study, a platelet-rich and fibrin-rich hydrogel was generated from expired platelet components that would have otherwise been transfused. The material contained physiological concentrations of transforming growth factor β1 (TGF-β1, platelet-derived growth factor AB (PDGF-AB), PDGF-BB, insulin-like growth factor-1 (IGF-1), fibroblast growth factor 2 (FGF-2), and epidermal growth factor (EGF). The effect of the hydrogel on wound repair was investigated in SKH-1 mice. Full thickness dorsal wounds were created on the mice and treated with the hydrogel at various concentrations. Immunohistochemical staining with CD31 (endothelial cell marker) revealed that wounds treated with the hydrogel showed significantly enhanced vascularisation in the wound bed. Moreover, high levels of interleukin-6 (IL-6) and KC (IL-8 functional homologue) in treated wounds were sustained over a longer period of time, compared to untreated wounds. We postulate that sustained IL-6 is a driver, at least partly, of enhanced vascularisation in full thickness wounds treated with the hydrogel. Future work is needed to explore whether this hydrogel can be utilised as a treatment option when vascularisation is a critical limitation. Statement of significance: The economic cost of wound repair is estimated in billions of dollars each year. In many cases time required to vascularise wounds is a major contributor to slow wound repair. In this study, we developed a blood-derived platelet- and fibrin-rich hydrogel. It contains a number of growth factors actively involved in spontaneous wound healing. This hydrogel significantly improved dermal repair and vascularisation in a full-thickness wound mouse model. This study provides an action mechanism for modulation of localised inflammation. Graphical abstract: Image, graphical abstract